Integration of the Theory of Work Adjustment and Al-Quranic Values in Islamic Career Counseling - Yulia Saputri; Aisha Satira Ardhi; Masril Masril (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to analyze the integrationTheory of Work Adjustment(TWA) with Qur'anic values ​​in Islamic career counseling. The development of the modern world of work presents various challenges, such as career uncertainty, anxiety about the future, low job readiness, and individual difficulties in adjusting to the demands of the work environment. This phenomenon shows that career counseling services need to pay attention not only to psychological aspects, but also to spiritual and moral dimensions. This study aims to: (1) analyze the concept of TWA in career counseling, (2) identify Qur'anic values ​​that are relevant to Islamic career development, and (3) examine the form of integration of TWA with Qur'anic values ​​in Islamic career counseling (4). Implications for Guidance and Counseling Services in Schools The method used isSystematic Literature Review(SLR) by collecting and reviewing various literature through Google Scholar, SINTA, Garuda, and national and international journals. Data analysis was conducted using the techniquecontent analysisusing a descriptive qualitative approach. The results show that the integration of TWA with Qur'anic values ​​results in a more holistic Islamic career counseling approach through the integration of psychological and spiritual aspects to support career maturity, job satisfaction, and well-being in this world and the hereafter